Differences in motor imagery time when predicting task duration in alpine skiers and equestrian riders - Louis, M.; Collet, C.; Champely, S.; Guillot, A. (Research Quarterly for Exercise and Sport, 2012)
Athletes' ability to use motor imagery (MI) to predict the speed at which they could perform a motor sequence has received little attention. In this study, 21 alpine skiers and 16 equestrian riders performed MI based on a prediction of actual performance time (a) after the course inspection, (b) before the start, and (c) after the actual performance. MI and physical times were similar in expert skiers during each imagery session, while novice skiers and novice and expert riders underestimated the actual course duration. These findings provide evidence that the temporal accuracy of an imagery task prediction depends on the performer's expertise level and characteristics of the motor skill.